Effect of PVDF-CA Ratio on Electrospun Membrane for Water–Oil Filtration Application - Alias, Mohamad Haziq; Misnon, Izan Izwan; Jose, Rajan (UI Scholars Hub, 2020)
Oil spillage and generation of industrial water–oil wastewater mixture ignite a focus on filtration technology. Electrospinning technique provides a versatile route in producing tunable diameter and pores in nanofiber filtration membrane development. In this work, polyvinylidene difluoride (PVDF) and cellulose acetate (CA) electrospun membrane at different concentration ratios were synthesized for water–oil filtration application. The polymeric solutions were characterized using viscometer and conductivity testing, whereas the membranes were analyzed using contact angle, tensile test, scanning electron microscopy (SEM), and filtration testing of oil (dichloromethane). Conductivity test showed a decreased conductivity along with decrement of CA ratio in the polymeric solution. The viscosity results showed a rising trend along with the increment of CA in the polymeric solution along with the decrement of PVDF ratio. SEM result showed that all membranes had a fiber diameter range of 210–485 nm and pore size range of 235–856 nm. The tensile test showed a decreasing tensile strength as the ratio of PVDF in the electrospun membrane decreased. The membrane with PVDF-to-CA ratio of 90:10 showed optimum performance for water–oil filtration with a flux of 14,111 Lm−2h−1 and oil recovery of 94%.